Improvement of the technology for surfactant synthesis by Аcinetobacter calcoaceticus ІМV В-7241 - Pirog, Tatiana; Konon, Anastasia (My University, 2015)
The aim of the work was to intensify the synthesis of surfactants by Acinetobacter calcoaceticus IMV-7241 cultivated on ethanol and other carbon substrates. A. calcoaceticus IMV-7241 was grown in the medium with mono- (ethanol, glycerol, liquid paraffin, n-hexadecane, glucose) and mixed substrates in the presence of organic acids or heavy metal cations (0.1–2.0 mM Cu2+, Cd2+, Zn2+, Pb2+). The synthesis of surfactants was evaluated by emulsification index of cultural liquid, conditional concentration and concentrations of extracellular surfactants, which were determined gravimetrically after their extraction from supernatant with the mixture of methanol and chloroform. It was shown that addition of citrate and fumarate (0.01%) at the end of exponential growth phase of A. calcoaceticus ІМV В-7241 in the medium with ethanol (2%) and the maintenance of neutral pH increased the surfactants’ concentration in 3.5 times (up to 6.0 g/l). The quantity of extracellular surfactants synthesized by the strain ІМV В-7241 in the medium containing mixture of n-hexadecane and glycerol (molar ratio 1:7) and C/N 30 was increased in 2.6–3.5 times in comparison with cultivation on corresponding monosubstrates. Addition of 2.0 mM Cu2+ at the stationary growth phase of A. calcoaceticus ІМV В-7241 in medium with liquid paraffin and n-hexadecane led to the increase of surfactants’ synthesis in 2.3–2.5 times compared with those in the medium without Cu2+. Approaches to intensification of surfactants’ synthesis by A. calcoaceticus ІМV В-7241 (including addition of biosynthesis precursors and cultivation on the mixture of substrates) can be used to increase the efficiency of microbial technologies.
Keywords: кафедра біотехнології і мікробіології; heavy metals; surface-active substances; intensification of biosynthesis; precursor of biosynthesis; mixture of substrate; мікробні поверхнево-активні речовини; інтенсифікація біосинтезу; попередники біосинтезу; змішані субстрати; важкі метали; микробные поверхностно-активные вещества; интенсификация биосинтеза; предшественники биосинтеза; смешанные субстраты; тяжелые металлы